BUDAYA MATRILINEAL DALAM KETERWAKILAN PEREMPUAN DI LEGISLATIF DAERAH KOTA BUKITTINGI - Dewi Kurnia Putri; Nur Hidayat - sardini; puji - astuti (Journal of Politic and Government Studies, 2022)
there are analytical tools used in formulating the influence of matrilineal culture on women's representation in the legislature. The analytical tool used here is a SWOT analysis. This study aims to analyze the influence of matrilineal culture on women's representation in the legislative body of Bukittinggi City, analyze matrilineal cultural factors in women's representation and formulate strategies in the context of matrilineal culture to increase women's representation in the DPRD Kota Bukittinggi. This study uses a qualitative research type. Data collection was carried out by in-depth interviews. The results of this study indicate that the Minang community does adhere to a matrilineal system but this system only applies to adat. In the world of politics, women have the same position as men, there are no privileges. There are many factors that prevent women from entering politics, but they have nothing to do with adat. One of the biggest factors for the low representation of women in the Legislative Council of Bukittinggi is the low interest of women to run for council members.